Hyperpolarization methods in NMR spectroscopy - Kuhn, Lars T. (Topics in Current Chemistry, 2013)
Elucidating Organic Reaction Mechanisms using photo-CIDNP Spectroscopy, by Martin Goez. Parahydrogen Induced Polarization by Homogeneous Catalysis: Theory and Applications, by Kerstin Münnemann et al. Improving NMR and MRI Sensitivity with Parahydrogen, by R. Mewis & Simon Duckett. The Solid-state Photo-CIDNP Effect, by Jörg Matysik et al. Parahydrogen-induced Polarization in Heterogeneous Catalytic Processes, by Igor Koptyug et al. Dynamic Nuclear Polarization Enhanced NMR Spectroscopy, by U. Akbey & H. Oschkinat. Photo-CIDNP NMR Spectroscopy of Amino Acids and Proteins, by Lars T. Kuhn.